An intelligent aid for the visually handicapped - Woo, Jervis Wen Qing (Nanyang Technological University, 2022)
With the increase in number of visually handicapped people in Singapore, there is a need to find a solution that will enable them to be able to traverse inside of buildings independently. In Singapore, most visually handicapped people use a white cane to navigate around, with only a small number of them owning guide dogs. This may be useful in environments where they are familiar with as they have gone through Orientation & Mobility Training and have been trained on how to walk in a particular route. This report examines the different types of technological navigational aid available on the market. However, little has been done to support the needs of people with visual impairment. A mobile application named BlindNav was successfully developed specifically for this project using iBeacon technology. It mainly uses the Received Signal Strength Indicators of the iBeacons and fingerprinting to navigate to the destination. The development of BlindNav will be explained in this report, together with its technical specifications, hardware requirements and programming codes that were implemented into the mobile application. Testing was performed and data were presented in this report to show the effectiveness of BlindNav as an Indoor Positioning System for the visually handicapped. BlindNav had achieved an accuracy of around 1 metre. An additional mobile application was developed in the event where the visually handicapped required any assistance. The pros and cons of BlindNav were discussed in detailed in the report. Recommendations were also presented in this report for future development of similar mobile applications.